(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Polycystic ovary syndrome is a most common female reproductive disorder, involving endocrine and metabolic disorders with unclear etiology. It may clinically be manifested in young women of reproductive age as oligo-ovulation, abnormal levels of reproductive hormones, clinical hyperandrogenism, hirsutism, male pattern baldness, acne, acanthosis nigricans, and polycystic ovaries, additionally having a long prodroma with detectable abnormalities that present as the metabolic syndrome like Insulin resistance, hyperinsulinemia, obesity, and dyslipidemia. Current treatment options are unable to manage PCOS and suffer from unwanted effects. The present study aimed to investigate the effect of nutraceutical formulation ovajal on dihydrotestosterone (DHT)-fructose-induced polycystic ovary syndrome (PCOS) in Sprague Dawley (S.D.) female rats. Prepubertal rats in the experimental group (except control) received coadministration of DHT (s.c.) and fructose(p.o.). Along with DHT+F other groups were treated with OV100 & OV200, clomiphene, and metformin, at a dose of 100 mg/kg p.o., 200 mg/kg p.o., 100 mg/kg p.o., & 200 mg/kg p.o., respectively for 90 days. Estrus cyclicity, OGTT, luteinizing hormone, follicle-stimulating hormone, insulin, testosterone, and estradiol serum levels were assessed. Ovary, uterus, abdominal fat, and subcutaneous fat were collected, weighed and an ovary histomorphology examination was done. Results showed that OV100 and OV200 reversed the DHT-fructose induced changes by significantly (p < 0.05) increasing serum FSH level, estradiol level and decreasing their body weight, ovary weight, uterine weight, serum luteinizing hormone level, testosterone level, oral glucose tolerance, irregular estrous cyclicity and no. of cystic follicles. However, the OV200 notably ameliorated the abnormalities of experimental PCOS. Our study findings demonstrate that ovajal formulation exerted preventive benefits in an experimental model of PCOS. Hence can be suggested in the management of PCOS.